2019
DOI: 10.1097/rli.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Retention of Gadolinium on Metabolism of Deep Cerebellar Nuclei After Repeated Injections of Gadodiamide in Rats

Abstract: Objectives: To determine potential metabolism and histological modifications due to gadolinium retention within deep cerebellar nuclei (DCN) after linear gadolinium based contrast agent injection (gadodiamide) in rats at 1 year after the last injection. Materials and Methods: Twenty rats received 20 doses of gadodiamide (0.6 mmol of gadolinium per kilogram each) over 5 weeks. They were followed at 1 week (M0), 6 weeks (M1) and 54-55 weeks (M13) post-injections to evaluate hypersignal on unenhanced T1weighted M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Indeed, no proof of tissue damage related to gadolinium deposition has been demonstrated so far by MRI studies using different techniques, 21,27 as well as by histological postmortem studies conducted on humans and animal models 5,15,17,18 . Furthermore, a recent study on a murine model by El Hamrani et al showed that retention of gadolinium after 20 intravenous doses of gadodiamide, mostly within DN, was not associated with detectable changes of metabolic biomarkers and histological abnormalities 19 . However, another preclinical in vitro study performed on a cellular line of human basal ganglia neurons demonstrated cell death at clinically relevant doses for GBCAs with lower kinetic stability (ie, linear), due to neurotoxic effects 28 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, no proof of tissue damage related to gadolinium deposition has been demonstrated so far by MRI studies using different techniques, 21,27 as well as by histological postmortem studies conducted on humans and animal models 5,15,17,18 . Furthermore, a recent study on a murine model by El Hamrani et al showed that retention of gadolinium after 20 intravenous doses of gadodiamide, mostly within DN, was not associated with detectable changes of metabolic biomarkers and histological abnormalities 19 . However, another preclinical in vitro study performed on a cellular line of human basal ganglia neurons demonstrated cell death at clinically relevant doses for GBCAs with lower kinetic stability (ie, linear), due to neurotoxic effects 28 …”
Section: Discussionmentioning
confidence: 99%
“…5,15,17,18 Furthermore, a recent study on a murine model by El Hamrani et al showed that retention of gadolinium after 20 intravenous doses of gadodiamide, mostly within DN, was not associated with detectable changes of metabolic biomarkers and histological abnormalities. 19 However, another preclinical in vitro study performed on a cellular line of human basal ganglia neurons demonstrated cell death at clinically relevant doses for GBCAs with lower kinetic stability (ie, linear), due to neurotoxic effects. 28 This difference between preclinical animal and in vitro studies might depend on the poorly understood complexities of cellular and extracellular in vivo microenvironment that needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 20 weeks from linear administration to a group of healthy rats, neurotoxicity was not detectable [47]. Moreover, an analysis of chosen metabolic markers (cellular homeostasis, excitatory neurotransmitter, and metabolites specific to a cellular compartment) with 1H-magnetic resonance spectroscopy (1H-MRS) and laser ablation ICP-MS revealed no significant metabolism and histological changes between gadodiamide and a control group [57]. On the other hand, some studies have found relevant alterations after GBCA administration in animal models.…”
Section: Toxicity Of Gadolinium Depositionmentioning
confidence: 97%
“…Res. Public Health 2021, 18, 7214 2 of 12 of incubation [6]. Such transmetalation and the release of Gd 3+ may cause toxicity in GBCA-deposited tissues, although the GBCA itself may also possibly cause toxicity.…”
Section: Introductionmentioning
confidence: 99%